2021
DOI: 10.1186/s12920-021-00994-z
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of lncRNA HIST1H2AG-6 and AIM1-3 in peripheral blood mononuclear cells is associated with newly diagnosed type 2 diabetes

Abstract: Background Type 2 diabetes mellitus (T2DM) is mainly affected by genetic and environmental factors; however, the correlation of long noncoding RNAs (lncRNAs) with T2DM remains largely unknown. Methods Microarray analysis was performed to identify the differentially expressed lncRNAs and messenger RNAs (mRNAs) in patients with T2DM and healthy controls, and the expression of two candidate lncRNAs (lnc-HIST1H2AG-6 and lnc-AIM1-3) were further validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…and lnc-AIM1-3) and the levels of FIN, FPG, HOMA-B and HbA1c-B [30]. In addition, a negatively correlation was observed between NFATc3 expression and HbA1c, FPG.…”
Section: Discussionmentioning
confidence: 82%
“…and lnc-AIM1-3) and the levels of FIN, FPG, HOMA-B and HbA1c-B [30]. In addition, a negatively correlation was observed between NFATc3 expression and HbA1c, FPG.…”
Section: Discussionmentioning
confidence: 82%
“…The expression level of lnc-HIST1H2AG-6 gene were significantly correlated with some features of T2DM. [18] High expression of LYPLA1 was associated with a poor prognosis in lung adenocarcinoma (LUAD). [60] In this study, in order to explore the functional annotations of 5 signature genes, the GSEA analysis found that they were associated with immune macromolecules such as proteasome, mitochondria and lysosome.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of lnc-HIST1H2AG-6 gene were significantly correlated with some features of T2DM. [ 18 ] High expression of LYPLA1 was associated with a poor prognosis in lung adenocarcinoma (LUAD). [ 60 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation